Active transcriptomic and proteomic reprogramming in the C. elegans nucleotide excision repair mutant xpa-1 - Kassahun, Henok (Landes Bioscience, 2013)
Oxidative stress promotes human aging and contributes to common neurodegenerative diseases. Endogenous DNA damage induced by oxidative stress is believed to be an important promoter of neurodegenerative diseases. Although a large amount of evidence correlates a reduced DNA repair capacity with aging and neurodegenerative disease, there is little direct evidence of causality. Moreover, the contribution of oxidative DNA damage to the aging process is poorly understood. We have used the nematode Caenorhabditis elegans to study the contribution of oxidative DNA damage and repair to aging. C. elegans is particularly well suited to tackle this problem because it has a minimum complexity DNA repair system, which enables us to circumvent the important limitation presented by the extensive redundancy of DNA repair enzymes in mammals.